THE EXPLORATION OF AUTONOMY SUPPORT IN LECTURER CONTEXT - Devani Laksmi Indyastuti (UNEJ e-Proceeding)
Autonomy support from organization, supervisor in lecturer context is still unclear and little getting attention. This study have purpose to explore how organization, supervisor should support lecturers in order to fulfill their autonomy. Autonomy is a basic psychological need that must owned by all human. This is a qualitative research. I used phenomenography to show many of autonomy supports based on the experiences of participant. The result shows that lecturers need consistent rules, procedures, and clear mechanism to do their job for supporting their autonomy. The other autonomy supports are facilitating all lecturers’ academic activity, minimizing surveillance, and procedural justice.